Flexible adhesives for automotive application under impact loading. (January 2015) - Kadioglu, Ferhat; Adams, Robert D.
Abstract: In automotive construction, adhesive bonding can be used for joining metals, plastics or combinations of the two, and it offers the further advantage that, because the joints are continuous, an overall increase in body stiffness is achieved, thus enabling thinner material to be used. Because of their ability to absorb energy adhesive joints can also contribute to the impacted system. The objective of this work is to investigate the behavior of a flexible adhesive under impact loading using the single lap joint configuration. This adhesive showed a high strain to failure with good strength. These features of the adhesive under impact loading improve structural crashworthiness. Results showed that the lap joint strength increases considerably under impact loading compared with those under quasi-static loading and that there is a relationship between the joint performance and the loading speeds.